The regulatory role of dietary ?-3 essential fatty acids on oxidant/antioxidant balance in rat hippocampus - Sarsimaz, M; Songur, A; Kus, I; Ozyurt, B; Gulec, M; Sogut, S; Akyol, O (John Wiley & Sons Ltd, 2003)
Omega-3 essential fatty acids (omega-3 EFA) contains eicosapentaenoic acid and docosahexaenoic acid (DHA). DHA is one of the building structures of membrane phospholipids of brain and necessary for continuity of neuronal functions. omega-3 EFA has been suggested to be protective against neuropsychiatric disorders including schizophrenia. This study proposed to assess the changes in superoxide dismutase (SOD), xanthine oxidase (XO), malondialdehyde (MDA), and nitric oxide (NO) in the hippocampus of rats fed with omega-3 EFA diet (0.4 g/kg/day) for 30 days. Eight control rats and nine rats fed with omega-3 EFA were decapitated under ether anesthesia, and hippocampus was removed immediately. Rats treated with omega-3 EFA had significantly lower XO activity (p<0.002) and NO level (p<0.0001) whereas higher SOD activity (p<0.002) and MDA levels (p<0.019) than the control rats. These results suggest that the dietary omega-3 EFA may act on the oxidant/antioxidant parameters in hippocampus. On the other hand, although the mechanism is not clear, omega-3 EFA may enhance one of the most important antioxidant enzymes, SOD. Further studies are needed to clarify the molecular mechanism involved and the therapeutic implication of omega-3 EFA in animal psychosis models and clinical studies.
Keywords: omega-3 essential fatty acids; superoxide dismutase; xanthine oxidase; lipid peroxidation; nitric oxide; schizophrenia therapy